Production of N-graphene by microwave N2-Ar plasma. (7th January 2016) - Dias, A; Bundaleski, N; Tatarova, E; Dias, F M; Abrashev, M; Cvelbar, U; Teodoro, O M N D; Henriques, J
Abstract: Self-standing N-graphene sheets were produced in low-pressure microwave N2 -Ar plasma. The graphene sheets were exposed to the plasma for various durations and doped with nitrogen atoms, which were incorporated into the hexagonal carbon lattice in pyridinic, pyrrolic and quaternary functional groups, mainly. Atomic nitrogen emissions at the substrate position in the plasma were detected using optical emission spectroscopy. Raman spectroscopy, x-ray photoelectron spectroscopy and transmission electron microscopy techniques were also applied for material characterization. Doping levels as high as 5.6% were achieved and an increase in the sp 2 /sp 3 ratio was observed for a relatively short exposure time.